2018
DOI: 10.3747/co.25.3805
|View full text |Cite
|
Sign up to set email alerts
|

A New Predictive Scoring System Based on Clinical Data and Computed Tomography Features for Diagnosing EGFR-mutated Lung Adenocarcinoma

Abstract: The mutation risk scoring system based on clinical data and ct features is noninvasive and user-friendly. The model appears to frame a positive predictive value and was able to determine the value of repeating a biopsy if tissue is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
1
8
0
Order By: Relevance
“… 40 , 41 Calcification in lung cancer may be primary and engulfed by the tumor, occur within areas of tumor necrosis, or manifest as calcium deposition following calcium secretion by the carcinoma itself. Cao et al 42 demonstrated that the sign of calcification in CT images showed no statistical significance between wild-type group and mutated group, which supported our results. However, another study found that calcification was an independent negative predictor of EGFR mutations and that, in adenocarcinoma, EGFR mutation is vital to the pathogenesis of nonmucinous but not mucinous BAC-type tumors, with the former leading to calcium deposition.…”
Section: Discussionsupporting
confidence: 90%
“… 40 , 41 Calcification in lung cancer may be primary and engulfed by the tumor, occur within areas of tumor necrosis, or manifest as calcium deposition following calcium secretion by the carcinoma itself. Cao et al 42 demonstrated that the sign of calcification in CT images showed no statistical significance between wild-type group and mutated group, which supported our results. However, another study found that calcification was an independent negative predictor of EGFR mutations and that, in adenocarcinoma, EGFR mutation is vital to the pathogenesis of nonmucinous but not mucinous BAC-type tumors, with the former leading to calcium deposition.…”
Section: Discussionsupporting
confidence: 90%
“…This study had a small sample, including only 15 cases of EGFR(+) and 103 cases of EGFR(−). Persistent subsolid nodules are the most common manifestations of early lung adenocarcinoma, and some previous studies also showed that LADCs with EGFR mutations showed significantly higher frequencies of subsolid nodules than those without EGFR mutations. Therefore, we focused on the relationship between CT‐based radiomics features and EGFR mutations in LADCs with subsolid nodules in a relatively large cohort.…”
Section: Discussionmentioning
confidence: 94%
“…A total of 34 retrospective diagnostic accuracy studies were included in the final analysis [9] , [12] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] . These articles assessed 10355 individuals; the sample size fluctuated between 64 and 864 patients per study.…”
Section: Resultsmentioning
confidence: 99%